Influence of Soybean Meal on Intestinal Mucosa Metabolome and Effects of Adenosine Monophosphate-Activated Protein Kinase Signaling Pathway in Mirror Carp (Cyprinus carpio Songpu) - Zhao, Jingyi; Xu, Qiyou (Frontiers in Marine Science, 2022)
This study aimed to explore influence of soybean meal on intestinal mucosa metabolism of Songpu mirror carp (Cyprinus carpio Songpu) by integrating liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based metabolomics. Fish meal (Con) was control group, soybean meal (Dou) group, AMPK activator (300 mg kg-1 Metformin, Met) and AMPK inhibitor (0.2 mg kg-1 Compound-c, c-Com) which added to soybean meal were experimental groups. The metabolome profiles of the intestinal mucosa were screened in fish fed diets Con, Dou, Met and c-Com on 7th and 59th d. The results were shown: compared with the Con group, the weight gain rate (WGR) of fish in experiment groups were significantly decreased (P < 0.05). Sphingosine was up-regulated in all experiment groups (P < 0.05). Oxidized glutathione was up-regulated in Dou on 7th d, Met on 7th and 59th d (P < 0.05), and that was not changed in c-Com (P > 0.05). Amino acids were reduced significantly and majorities of sugar metabolites were up-regulated in all experiment groups, except Dou on 7th d (P < 0.05). Up-regulation of ADP and AMP were identified in Dou on 59th d, Met on 59th d, c-Com on 59th d (P < 0.05). Compared with the Dou group, sphingosine was up-regulated in Met on 59th d, c-Com on 7th and 59th d (P < 0.05), however, which was down-regulated in Met on 7th d (P < 0.05). Oxidized glutathione and isocitrate were up-regulated in Met on 7th d (P < 0.05). L-Valine, L-histidine, and L-isoleucine were increased in Met on 59th d (P < 0.05). Nucleoside metabolites and ADP were up-regulated in c-Com on 7th d (P < 0.05). In conclusion, by affecting AMPK and FoxO signaling pathway, soybean meal influenced intestinal mucosa metabolic processes, including lipid, amino acid, sugar, energy metabolism, apoptosis and oxidative injury to reduce growth performance in carp. Metformin could aggravate oxidative damage, alleciated apoptosis for the short term, and aggravate apoptosis, improve carbohydrate catabolism and amino acid anabolism for the long term. Compound-c exacerbated apoptosis and repaired oxidative damage for the whole time, enhanced nucleoside catabolism, and inhibited fat decomposition for the long term.